Towards understanding and improving the safety of informal public transport in Sub-Saharan Africa : a real-time sensing and reporting system for minibus taxis - Zeeman, Adriaan Siebrits (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)--Stellenbosch University, 2013.